2016
DOI: 10.15761/cmid.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Infection in Mexican Children with Rheumatic Diseases

Abstract: Rheumatic diseases (RD) patients have fourfold increased risk for tuberculosis infection compared with the general population. The aim of this work is to determine the prevalence of Latent Tuberculosis Infection (LTBI) in Mexican children and adolescents with RD. Descriptive exploratory study on 29 patients admitted in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…pregnancy and also the placenta accreta 14,15 . In a woman with placenta praevia in the first pregnancy the risk of developing placenta praevia is 1-3% in contrast to a multigravida where the risk is 30-51% higher 16 .…”
Section: Research Articlementioning
confidence: 99%
“…pregnancy and also the placenta accreta 14,15 . In a woman with placenta praevia in the first pregnancy the risk of developing placenta praevia is 1-3% in contrast to a multigravida where the risk is 30-51% higher 16 .…”
Section: Research Articlementioning
confidence: 99%
“…41 The World Health Organization defines latent Mycobacterium tuberculosis infection or latent TB infection (LTBI) as a state of persistent immune response to stimulation by Mycobacterium tuberculosis (M. tb) antigens without evidence of clinical manifestations of active TB. 1,42 In cases of LTBI, despite the absence of symptoms, there is a risk that patients with rheumatic diseases will develop TB disease, especially in the first two years after the primary infection. 1,42,43 If LTBI is not diagnosed and treated appropriately, activation occurs in 5-10% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…1,42 In cases of LTBI, despite the absence of symptoms, there is a risk that patients with rheumatic diseases will develop TB disease, especially in the first two years after the primary infection. 1,42,43 If LTBI is not diagnosed and treated appropriately, activation occurs in 5-10% of cases. 1,42,43 There are two tests available for the diagnosis of LTBI, the tuberculin skin test (TST), and the interferon-gamma release assay tests (IGRAs).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the sensitivity and specificity of TST and IGRAs in the diagnosis of LTBI represents a great difficulty, because in that setting there is not a comparative "gold standard test"; on the other hand, it is easier to define them for active tuberculosis, by having more specific elements and benchmarking objectives such as MTB cultures or molecular tests such as the MTB-Xpert MTB-RIF assay, or the combination of a TB-compatible clinical picture with findings in imaging studies, positive Ziehl–Neelsen staining smears and/or histological studies. However, the sensitivity and specificity of both tests (TST and QFT) in the pediatric population has been compared in several investigations [ 6 , 19 – 22 ]. The TST showed a lower sensitivity of 78% and a specificity of 49%, while the QFT test had a sensitivity of 89% and a specificity of 96% for LTBI.…”
Section: Discussionmentioning
confidence: 99%
“…The TST showed a lower sensitivity of 78% and a specificity of 49%, while the QFT test had a sensitivity of 89% and a specificity of 96% for LTBI. The latter has a lower percentage of false positives related to BCG vaccination and cross-reaction with other mycobacteria; better tolerability among children; greater speed and accuracy in the results [ 16 18 , 20 , 22 ]. In our study, we found a higher proportion of QFT positivity compared to TST, both in the general casuistry and in the different subgroups analyzed (age, history of BCG vaccination, contacts of active TB cases and immune status categories.…”
Section: Discussionmentioning
confidence: 99%